2014
DOI: 10.1159/000355774
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in a Single Pediatric Intensive Care Unit in Poland: A Retrospective Study

Abstract: Background/Aims: The recent improvements of management of patients in pediatric intensive care units (PICU) are associated with improved outcome. However, this decrease in mortality is associated with an increased number of children with acute kidney injury (AKI), especially in patients with multiorgan failure. Methods: The report presents a retrospective analysis of 25 cases of AKI (assessed based on the pRIFLE criteria) in PICU within 7 years. Results: AKI was diagnosed in 1.24% of all hospitalized children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…The mortality rate is high among children admitted to ICUs who are diagnosed with AKI, with reported rates ranging from 40 to 46 % [ 19 – 21 ]. A study conducted in Poland showed that AKI is associated with a 4.4 times higher risk of death compared with the total mortality rate for PICU patients [ 22 ]. Another study conducted in Canada has reported that AKI is an independent risk factor for mortality, a longer length of hospital stay and prolonged mechanical ventilation in critically ill children [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate is high among children admitted to ICUs who are diagnosed with AKI, with reported rates ranging from 40 to 46 % [ 19 – 21 ]. A study conducted in Poland showed that AKI is associated with a 4.4 times higher risk of death compared with the total mortality rate for PICU patients [ 22 ]. Another study conducted in Canada has reported that AKI is an independent risk factor for mortality, a longer length of hospital stay and prolonged mechanical ventilation in critically ill children [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher risk adjustment for congenital heart surgery (RACHS-1) scores (3 and above) 12,13 Presence of cyanotic lesions 10 Uncorrected or residual cardiac defects 4 Cardiopulmonary bypass (nonpulsatile flow; inflammatory cascade) 12 Longer cardiopulmonary bypass time 12 Hypothermic circulatory arrest 34 Requirement of inotropic support 10,12 Low cardiac output syndrome 12 Prolonged ventilator requirement 14 Need for extracorporeal membrane oxygenation (ECMO) 35 Early fluid overload 14…”
Section: Hemodynamicmentioning
confidence: 99%
“…Acute renal failure (ARF) is a very common event which usually leads to development of chronic kidney disease [1,2]. Ischemia/reperfusion injury (IRI) is an unavoidable consequence of organ transplantation procedure [3].…”
Section: Introductionmentioning
confidence: 99%